Aekonomiczność efektywności zarządzania zasobami ludzkimi - Strużyna, Janusz; Majowska, Magdalena; Ingram, Tomasz (Wastefulness of Human Resources Management Effectiveness, 2006)
In the present article, the authors made an attempt to improve the general understanding of the issue of human resource management effectiveness. The complex nature of the relationship between human resource management and the performance of an organization has been highlighted and discussed. The authors focused also on different ways of performance measurement applied in research and in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 382-389